Plasma Wakefield Accelerator Research 2019 - 2040: A community-driven UK roadmap compiled by the Plasma Wakefield Accelerator Steering Committee (PWASC) - Hidding, B; Hooker, S; Jamison, S; Muratori, B; Murphy, C; Najmudin, Z; Pattathil, R; Sarri, G; Streeter, M; Welsch, C; Wing, M; Xia, G (2019)
The acceleration gradients generated in a laser- or beam-driven plasma wakefield accelerator are typically three orders of magnitude greater than those produced by a conventional accelerator, and hence plasma accelerators can open a route to a new generation of very compact machines. In addition, plasma-based accelerators can generate beams with unique properties, such as tens of kiloamp peak currents, attosecond bunch duration, ultrahigh brightness and intrinsic particle beam-laser pulse synchronization. In this roadmap we review the status of plasma accelerator research in the UK. We outline potential applications, describe the research and development required to enable those applications, and discuss synergies with related areas of research. We also set-out the resources required to realise these ambitions and provide a timeline for advances in the key areas.